MENYEGERAKAN PENGUBURAN JENAZAH PERSPEKTIF HADIS - Ayi Latifatul Alimah (IAIN Syekh Nurjati Cirebon, 2019)
The law of looking after jenazah is fardu kifayah. And the law of burying jenazah is obligatory. Rasulullah recommended to bury jenanazah as soon as possible. But, in the practice of society, it is still postponed by the reasons: waiting for family, following tradition, or dong autopsy to jenanazah.According to background above, the assesment that is researched including: 1. The quality and the quantity of sanad and matan Hadis. 2. The meaning and the understanding of Hadis. And 3. The relevance of Hadis to modern era. The purposes of this research are: 1. Knowing the quality and the quantity of burying jenazah quickly. 2. Knowing the meaning of Hadis as textual and contextual. 3. Knowing the relevance of new society. The kinds of this research are refer to some library research and field research. The theory that is used is the the theory that is bergained by Yusuf Qardawi. This method is explaining how can understand Hadis from textual and contextual. thus, it can produce relevant meaning and understanding. The resulst of this research are : 1. From the quality, Hadis burying jenazah quickly is included to Hadis aḥad ʻazīz. It is taled (diriwayatkan) by using two ways of rawi. Those are, abu said al khudri and abu hurairah. 1. From the quality of Hadis, the strip of abu said al kudri is included to category Hadis of ṣaḥīḥ li dzatihi,, and the strip of abu hurairah is included to category of ṣaḥīḥ li gairihi.. 2. The meaning and the understanding Hadis have different opinion. First, do quickly, on the Hadis is doing work quickly, slowly, or standarly. Second, do quickly in the way of taking up/ taking along jenazah, and third, looking after untill burying jenazah. 3. The relevance of Hadis to the new society, this Hadis can be hujjah to bury jenazah or postpone jenazah.Keywords: Hadis, Jenazah, Relevance.